On the Development of an Anti-Sloshing System for Sub-Orbital Vehicle Cryogenic Tanks - Pinto, Adriana Raquel Moura (2023)
Sloshing has been a topic of study since the beginning of the 1960s as it represents a real problem for various means of transport, such as tanks, airplanes, and rockets. This phenomenon corresponds to the unwanted movement of liquid within a reservoir when it suffers a perturbation, leading to unwanted loads that affect the vehicle’s stability. This dissertation aims to understand the influence of sloshing when applied to the cryogenic tanks of the sub-orbital vehicle within the scope of the VIRIATO project. The main objective is to develop an anti-sloshing system to be used in the case in question. To reduce the effects of sloshing, devices called baffles are commonly applied. There are several baffle configurations, the most common being rings. Firstly, the Miles equation developed by Bauer was implemented, using Python, carrying out a study of the damping of different baffle configurations with constant spacing. To understand the influence of different spacing, Powell’s method was used to optimize the configurations. Four configurations were obtained and subsequently implemented in the numerical and experimental models. The numerical model was implemented in ANSYS Fluent® using a transient and pressurebased analysis with a VOF model. To model turbulence, the k-e model was used. The experimental model, completely developed at INEGI, consists of a structure of extruded aluminum profiles an acrylic tank, and machined aluminum blocks. The anti-sloshing system was designed to facilitate changing settings. Excitation was provided by an electrical model coupled with a Scotch-Yoke mechanism. The numerical and experimental models allowed to obtain the variation of the free surface over time. The efficiency of implementing the baffles was corroborated by observing a rapid stabilization of the free surface as soon as the movement stopped. Furthermore, the analytical prediction that a higher number of baffles dampens the liquid more was corroborated.